Privatization and Structural Adjustment in the Arab Countries : Papers Presented at a Seminar held in Abu Dhabi, United Arab Emirates, December 5-7, 1988. (International Monetary Fund, 1989)
This seminar volume, edited by Said El-Naggar, examines the challenge that Arab countries with large public sectors face in placing the privatization process within the wider context of structural change.